THE CHARACTERIZATION OF GRINDING FORCES - Fielding, E.F. (The South African Journal of Industrial Engineering, 2012)
Traditionally the grinding process has been a finishing process and the operating parameters and the resuns obtained in this mode are well known. However, wHh the advent of more modern techniques in grinding, there is a need for a greater understanding of the process and in particular a need to be able to predict the forces in grinding. The work reported here is part of an overall programme to study the effects of different dress leads, wheel formulations and metal removal rates on grinding ratios, surlace finish and grinding forces. The work so far has led to the development of empirical relationships based on the various factors in the dressing and grinding operations, these empirical relationships are more easily applied than the relationships developed by other researchers that rely on measurements obtained during testing. The work is now being extended to develop a theoretical derivation on the same principles, the implications of which will be discussed in the paper.